2013
DOI: 10.5093/cl2013a10
|View full text |Cite
|
Sign up to set email alerts
|

Cuidadoras de familiares dependientes y salud: influencia de la participación en un taller de control de estrés

Abstract: Las tareas de cuidado a dependientes merecen ser objeto de estudio y atención por representar un factor de riesgo para la salud. Por ello analizamos los efectos de ser cuidadora familiar y asistir a un curso de control del estrés, así como la incidencia de dos covariables consideradas relevantes, como son los pensamientos disfuncionales y el tiempo prestando cuidados. Analizamos una muestra de 219 asistentes a talleres psicoeducativos a la que se aplicaron tres instrumentos: cuestionario sociodemográfico, cues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The most common components in all these trials are psychoeducational, ACE, cognitive behavioral therapy (CBT), and social support (SS) interventions, which, in turn, have the most significant effect on the variable of caregiver burden and improvement of quality of life (QoL). These results are supported by other studies where psychoeducation and the application of ACE and SS techniques have a positive effect on caregiver burden and the stress associated with caregiving, improving the QoL of the IC ( 39 , 61 63 ).…”
Section: Discussionsupporting
confidence: 84%
“…The most common components in all these trials are psychoeducational, ACE, cognitive behavioral therapy (CBT), and social support (SS) interventions, which, in turn, have the most significant effect on the variable of caregiver burden and improvement of quality of life (QoL). These results are supported by other studies where psychoeducation and the application of ACE and SS techniques have a positive effect on caregiver burden and the stress associated with caregiving, improving the QoL of the IC ( 39 , 61 63 ).…”
Section: Discussionsupporting
confidence: 84%
“…It is clearly established that the absolute majority of people who care for relatives are women (IMSERSO, 2005) and that they have worse health themselves. They show a greater number of anxiety and depression symptoms, various somatic symptoms such as back pain, and a higher prevalence of some chronic diseases (Colombo, Llena-Nozal, Mercier & Tjadens, 2011;Saavedra, Bascón, Arias, Calderón & Mora, 2013). The limited literature available indicates that caregiv-ers with burnout are at a greater risk than their more professionalized counterparts -nurses-, even if they work in the same context (Gerhard, 2000).…”
Section: Caregivers and Healthmentioning
confidence: 99%
“…These interventions clearly improved knowledge; however, stress and burnout seemed not to be improved in a significant way (Spector et al, 2016). On the other hand, there is some partial evidence of the effectiveness of stress management courses for family caregivers Ruiz-Robledillo & Moya-Albiol, 2015;Saavedra, et al, 2013). The aim of these courses or workshops is to provide family caregivers with strategies and resources to cope with the stress that caregiving tasks entail.…”
Section: Training Programs For Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, health indicators are directly related to perceived overburden, such that the heavier the burden is perceived, the greater the deterioration in health. Specific studies done with family caregivers of Alzheimer's patients, which evaluated the general health condition of the patients, found that around 65% of the cases evaluated needed specialized attention (Saavedra et al, 2013).…”
Section: Introductionmentioning
confidence: 99%